Folding of cones - Koh, Owen Hao Yuan. (2009)
A new type of foldable structure is presented, which is conical in shape and has triangulated patterns on its surface. Accomplishment in this area of research means conical structure can be compressed in order to minimise space usage. Origami patterns have been designed in order to make the cones folded as compactly as possible in the axis direction. Also, the mechanical characteristics of the origami patterns were tested by experiments in order to optimise the compressive force used. Three conical patterns (Design K, L and M) were chosen. Parameters of each pattern are determined by the diameter, height, the number of sides (N) and the angles α, β and Θ. Polypropylene was found to be the suitable specimen material. Patterns were imprinted on the polypropylene sheet and it was folded along the mountain and valley folds. The edges of the sheets were joined to form thin walled cones and experiments were conducted on Instron 5565 to observe the mechanical energy required for compression of these patterns and its association with the number of sides and the folding length. It was found that the compressive load increases with the number of sides of the conical prototypes. Also, different patterns with the same number of sides require different compression loads. Further investigation is done to confirm the above results, and it was later found that there is proportional relationship between the folding length and mechanical energy involved in the compression process. It was also discovered that patterns affect the energy slightly.